Artificial Intelligence Model for Human Capital Management - Didik Hadiyatno; Dwi Susilowati; Nadi Hernadi Moorcy; Imam Arrywibowo; Tutik Yuliani (Jurnal Penelitian Pendidikan IPA, 2023)
Artificial Intelligence is a technology that allows machines to learn and adapt quickly from given data without having to be explicitly programmed. AI has found its place in many industries and has great potential to improve the efficiency of human resources within organizations. In this article, we will discuss how the use of artificial intelligence can help improve human resource efficiency. This review is a literature search with an elaborative approach. This approach is a methodological effort by organizing the logic flow of the discussion with various compatible literature sources. Reliable literature sources come from journals, books, articles, and other sources relevant to this discourse. The result of the study is that human resource management needs to adjust to the needs of the organization and adjust the culture or corporate culture to the technological culture. Human interaction with machines is an inevitable necessity. The existence of artificial intelligence is very helpful in human resource management, for example in recruitment systems, training, data analysis, performance analysis, and operational duty efficiency.